Stigmatisation and neoliberal management of poverty. Why we talk about poverty and not about inequalities - Sales Campos, Albert (Revista Española de Desarrollo y Cooperación, 2024)
In post-industrial societies, poverty and marginalisation can no longer be considered cyclical or cyclical phenomena. Successive capitalist crises have left in their wake a growth in extreme forms of precariousness and a state reaction based on the stigmatisation and criminalisation of social groups that are systematically excluded from the benefits of economic growth.Using a few examples, this article starts from the "discovery of the underclass" in the era of the welfare state and the construction of poverty as an object of intervention by social democratic public policies, and uses a few examples to explore the stigmatising discourses that justify the neoliberal management of poverty.
Keywords: poverty; criminalisation; stigma; inequalities; social services; marginality